PROFIL BERPIKIR REFLEKTIF SISWA BERGAYA KOGNITIF VISUALIZER DENGAN KEMAMPUAN MATEMATIKA TINGGI DALAM MENYELESAIKAN SOAL HOTS - Soffil Widadah Widadah (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
Students' failures in solving HOTS questions in general can be caused by students' inaction according to personal experience, not analyzing and classifying knowledge to evaluate actions, and not reflecting or rethinking what has been done to draw conclusions. This is a reflective thinking phase, where reflective thinking is a process of gathering information and thinking logically to make decisions and evaluate the decisions that have been taken. This study aims to describe the reflective thinking profile of Visualizaer students with high mathematical abilities in solving HOTS questions. This exploratory research produced data that the subject could not solve the problem in various ways, meaning that the subject did not meet one indicator of the five indicators of reflective thinking. Thus it can be said that in the reflective thinking phase the subject has not analyzed and classified knowledge to evaluate actions.